(untitled) (VITAE Academia Biomédica Digital, 2004)
This study was carried out to assess the effect of Eicosapentaenoic-Docosahexaenoic Acids (EPA/DHA) and Choline Bitartrate-Inositol (CHO/INO) supplementation on ADHD-children by evaluating their MRS profiles. Basal Ganglia?s MRS was performed at the beginning of the study and after 6-month EPA/DHA and CHO/INO treatment using a 1.5 Tesla Magnetic Resonance System. The results show a significant increase in the signal intensities of Choline-containing compounds and a significant raise in Choline/Creatine ratio after 6-month-therapy on ADHDchildren, which correlate with the improvement of their capacities and abilities. The link between MRS-based EPA/DHA and CHO/INO monitoring and the improvement of the numerical, verbal, visual, hearing and concentration capacities may also provide a fertile ground for developing an EPA/DHA plus CHO/INO based supplementation therapy and predicting its efficacy to upgrade ADHD-children?s cognitive abilities.